سايكس – بيكو الإعتبارات الجيوبولتيكية وإنعكاساتها على مصير كوردستان - مصطفی, فؤاد حم خورشید; توفیق, جزا (Sulaimani Journal for Humanities, 2018)
Abstract This article is about the Sykes_ picot agreement concluded between the great powers (Britain, France and Russia), and how they divided the domains of the Ottoman Empire among themselves the division is viewed from a geopolitical and geographic perspective. The focus has been on the division of that part of Kurdistan that was under Ottoman hegemony into British and France controlled portions, regardless to the will and without asking the opinion of its local population. The research is based on several geographic maps to explain the issue.